O processo de inclusão da criança com fissura labiopalatina nas escolas Santa Clara e Ascendendo as luzes (CEPAL), no município de Abaetetuba-PA - FERREIRA, Müller Júnior Sousa (2022)
This study aims to discuss the inclusion process of children with cleft lip and palate, with emphasis on the conditions of interaction, development and learning. For this, we take as a locus two schools in the municipality of Abaetetuba-Pará, which serve students with this malformation, with a view to educational and inclusion processes in these schools. The qualitative research included data collection based on observations and interviews with educators, parents and students. Also, my own life story was useful for the debate, as I have a cleft lip and palate. In the theoretical framework, issues of inclusion, teacher training, cleft lip and palate were taken further by authors, such as Aranha (1995; 2000; 2001), Arroyo (2015; 2017), Buffa (2009), Freire (2016), Gadotti (2007), Louro (2014), Mantoan (2003; 2013), (Silva (2018), Stainback (1999). After analyzing the data, the results obtained point out that the person with cleft lip and palate experiences in their school educational process particular situations that depend on at school he feels more observed and welcomed in this environment, which resonates with peculiar aspects with a tendency towards the invisibility of his life, in fullness.